Dampak jumlah penduduk, upah minimum dan indeks pembangunan manusia terhadap kemiskinan: Peran ZIS sebagai variabel moderasi di Jawa Tengah - Balqis, Zalfa Nabila Putri; Nurhadi, Bayu (Journal of Economics Research and Policy Studies, 2025)
Poverty is an individual problem in society, where the poor quality of existing resources, minimum wages that do not meet the cost of living, and population growth continue to increase, affecting competitiveness and making it difficult to meet daily needs. The impact of the decline in the number of poor people is the essential growth factor in the selection of regional development strategies and tools, including efforts to address the decline in the number of poor people in Central Java. This study is quantitative, using annual secondary data from 2018-2023 sourced through the website of the Central Java Provincial Statistics Agency and the annual report of the Central Java Provincial BAZNAS. The analysis method used in this study is moderated regression analysis. The results of this study prove that the population variable has a positive insignificant effect on poverty, the minimum wage variable has a positive insignificant impact on poverty, and the human development index variable has a significant adverse effect on poverty. In contrast, the ZIS variable is unable to moderate the population against poverty, ZIS is unable to moderate the minimum wage against poverty, and ZIS is able to moderate the HDI against poverty.